Effect of Cyanobacteria Nostoc calcicola on antioxidant system in soybean - Chung, Mai Van; Thanh Huyen, Mai Thi; Truong Giang, Dinh Thi (Vietnam Journal of Science and Technology, 2016)
Strain Nostoc calcicola HN9 of Cyanobacteria, which was in static culture, was collected biomass in log phase and death phase to exam its effect on the antioxidant system of soybean [Glycine max (L.) Merr. “Nam Dan”] in the vegetative stages. Suspension of HN9 in death phase plays as an unfavourable factor that caused to oxidative stress in soybean leaves with a burst of superoxide anion radical (O2.-) in stage V1 (each seedling has one unrolled trifoliolate leaf) and hydrogen peroxide (H2O2) in stage V3 (seedlings have two unrolled trifoliolates enclosing auxillary buds). In HN9-treated plants, total phenolics, a non-enzymatic antioxidant, was early induced to high content, whereas generation of ascorbic acid was inhibited; parallel, activity of enzymatic antioxidants such as superoxide dismutases (SOD), catalase (CAT), ascorbate peroxidases (APX) and polyphenol oxidase (PPO) were induced during the vegetative stages. An enhancement of SOD, CAT, and APX firmly regulated ROS products to avoid oxidative damage, reduced cellular damage, and allowed them to play crucial functions in signal transduction to increase soybean tolerance. The defensive role of PPO should be more clarified in the prospective studies. Different from above effects of cyanobacteria in death phase, suspension of HN9 in log phase only raised content of ascorbic acid, and induced activity of SOD and APX, however, its stimulated level was lower than that in death phase. Lack of convinced evidences discribed how strain HN9 in log phase affected (stimulated or inhibited) to biosynthesis of total phenolics and activity of CAT and PPO.